Efektivitas Penerapan Metode Pembelajaran Flipped Learning terhadap Kemampuan Berpikir Kritis Mahasiswa Keperawatan - Fitri Apriani; Alfi Syahri; Siti Damayanti; Orita Satria (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
The quality of education is increasing along with technological developments, one of which is nursing education which is experiencing rapid changes. Nursing students must have the ability to think critically to integrate various sources of knowledge in order to solve problems creatively and logically. Nursing education requires learning methods that enable students to actively address various nursing problems that arise in clinical practice. Flipped learning or reverse learning is a learning model that requires lecturers to transfer lectures directly from the classroom to individual study rooms (at home) with the help of technology. The purpose of this study was to analyze the effectiveness of applying the flipped learning method to the critical thinking skills of nursing students. Type of quantitative research with a quasi-experimental design with a non-equivalent control group pre-test post-test approach. The sampling technique used was consecutive sampling, namely all students in class A and B in the third semester of the Bachelor of Nursing Study Program. This research started from the preparation stage by preparing flipped learning model materials in the form of modules, power points and videos as well as preparing instruments on the Critical Thinking Disposition Self-Rating Form (CTDSRF) to measure critical thinking skills. Data analysis used paired t-test and t-test for independent groups to determine the effectiveness of the flipped learning method on critical thinking skills of nursing students. The results of both the intervention and control group studies were 0.001 ˂ 0.05, which means that the application of the flipped learning method was able to improve critical thinking skills. Flipped learning is more effective in improving the critical thinking skills of nursing students compared to conventional learning, where the lecturer makes materials in the form of narratives, power points and videos. Flipped Learning is one of the selected learning models as a feasible learning model to apply.